Qisas Reorientation (A Study about Sanctions in Criminal Act of Murder: a Comprehension from Hermeneutics Philosophy) - Mahmutarom H R (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
This paper tries to deeply investigate about the qisas reorientation, especially from the hermeneutics philosophy and its relation to the sanctions in criminal act of murder. Qisas, related to the Islamic law, has showed the principle of balance, legality, proportionality, reconciliation, transpiration and equality. Eventhough qisas has many benefits for both the victim and the criminal actor, it need a further study to considere it for the criminal law renewal in Indonesia. Keywords: qisas, reorientation, hermeneutic, murder sanction.